Classification of Moufang Loops of Odd Order pq3. - Balasingam Gnanaraj, Andrew Rajah (Universiti Sains Malaysia, 2014)
An open problem in the theory of Moufang loops is to classify those loops which are minimally non associative, that is, loops which are non associative but where all proper subloops are associative. A related question is to classify all integers n for which a minimally nonassociative Moufang loop exists.